Defrosting for air source heat pump : research, analysis and methods - Song, Mengjie; Deng, Shiming (Woodhead Publishing in energy., 2019)
Defrosting for Air Source Heat Pumps: Research, Analysis and Methods presents a detailed analysis of the methods, processes and problems relating to defrosting, a necessary requirement to maintain the performance of ASHP units. Readers will gain a deeper understanding of control strategies and system design optimization methods that improve the performance and reliability of units. The book discusses the most recent experimental and numerical studies of reverse cycle defrosting and the most widely used defrosting method for ASHP. Techno-economic considerations are also presented, as is the outlook for the future. This book is a valuable resource for research students and academics of thermal energy and mechanical engineering, especially those focusing on defrosting for ASHP, heating, ventilation and energy efficiency, as well as engineers and professionals engaged in the development and management of heat pump machinery. Includes MATLAB codes that allow the reader to implement the knowledge they have acquired in their own simulations and projectsDiscusses experimental and numerical studies to provide a well-rounded analysis of technologies, methods and available systemsPresents techno-economic considerations and a look to the future